The Effect of Profitability, Liquidity, and Leverage on Financial Distress in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Muhammad Shulhan Ma’arif (Golden Ratio of Data in Summary, 2026)
This study aims to examine the effects of profitability, liquidity, and leverage on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Using a quantitative research approach, a total of 49 manufacturing companies were selected as the research sample through purposive sampling. Financial distress was measured using the Altman Z-Score model, while profitability was proxied by Return on Assets (ROA), liquidity by the Current Ratio (CR), and leverage by the Debt-to-Equity Ratio (DER). The research hypotheses were tested using multiple linear regression analysis with SPSS software. The empirical findings indicate that profitability and liquidity have significant negative effects on financial distress, whereas leverage has a significant positive effect on financial distress. Furthermore, the results of the simultaneous test demonstrate that profitability, liquidity, and leverage collectively have a significant effect on financial distress. These findings highlight the critical role of financial performance in predicting financial stability and financial distress risk among manufacturing companies.